Developmental epigenetic programming of adult germ cell death disease: Polycomb protein EZH2–miR-101 pathway. (November 2016) - Siddeek, Bénazir; Lakhdari, Nadjem; Inoubli, Lilia; Paul-Bellon, Rachel; Isnard, Véronique; Thibault, Emmanuelle; Bongain, André; Chevallier, Daniel; Repetto, Emanuela; Trabucchi, Michele; Michiels, Jean-François; Yzydorczyk, Catherine; et al.
Aim: The Developmental Origin of Health and Disease refers to the concept that early exposure to toxicants or nutritional imbalances during perinatal life induces changes that enhance the risk of developing noncommunicable diseases in adulthood.Patients/materials & methods: An experimental model with an adult chronic germ cell death phenotype resulting from exposure to a xenoestrogen was used.Results: A reciprocal negative feedback loop involving decreased EZH2 protein level and increased miR-101 expression was identified. In vitro and in vivo knockdown of EZH2 induced an apoptotic process in germ cells through increased levels of apoptotic factors (BIM and BAD) and DNA repair alteration via topoisomerase 2B deregulation. The increased miR-101 levels were observed in the animal blood, meaning that miR-101 may be a part of a circulating mark of germ cell death.Conclusion: miR-101–EZH2 pathway deregulation could represent a novel pathophysiological epigenetic basis for adult germ cell disease with environmental and developmental origins.